The validity and reliability of intestinal temperature during intermittent running - Gant, N.; Atkinson, G.; Williams, C. (Medicine & Science in Sports & Exercise, 2006)
Purpose: In many sporting and occupational settings, measuring core temperature using invasive methods is not practical. In these circumstances, ingestible temperature sensor capsules are a promising alternative. To date, no researcher has investigated the validity of intestinal temperature (Tint) during free running or examined the between-trial reproducibility of this technique. Therefore, in two investigations, we examined the validity and reliability of Tint during prolonged intermittent shuttle running.